Shaped Bessel beam singulation of glass substrates - Chia, Hao Guang (Nanyang Technological University, 2022)
Increasingly the use of laser has been the preferred method for cutting glass in industries. In contrast to conventional methods such as waterjet cutting and diamond saw cutting, laser glass cutting is a non-contact cutting technique. This makes it possible to cut thin glass less than 1mm thick because no pressure is applied to the glass during the cutting process, which is often the cause of crack propagation. Laser glass cutting generates heat and vaporises glass through the mechanism of photon absorption. However, the heat generated can cause chipping and debris along the cut line. In addition, the area surrounding the cut often has heat damage, which alters the material's mechanical properties. Previous studies showed the advantage of using a Bessel beam for glass cutting applications as it can achieve a higher material remover rate than the Gaussian beam. In addition, the extended Depth of Focus (DOF) of the Bessel beam has also been shown to reduce heat damage on the material as a lower number of cutting passes are required during the cutting process. The Deepcleave module, made by HOLO /OR, claims even better glass cutting quality using a shaped Bessel beam to remove the interference pattern caused by an ordinary Bessel beam. However, the use of a shaped Bessel beam to improve the cut quality of glass and the method used to generate a shaped Bessel beam in the Deepcleave module have not been adequately studied. This report examined the Deepcleave module and its application for glass cutting. Experiments conducted showed that the Deepcleave module focuses the interference pattern onto the central axis of a Bessel beam to produce a higher intensity beam than the original Bessel beam. In contrast to previous studies using a refractive axicon lens to shape a Bessel beam, the Deepcleave module uses a Diffractive Optical Element (DOE) paired with a Plano-convex lens to produce a shape Bessel beam. The DOE, a lens with microstructure patterns on the surface of the lens used in the Deepcleave module, was analysed and shown to be a diffractive axicon. Further experiments verified that the depth of focus produced by the Deepcleve module was 1 mm as marketed by HOLO /OR. However, the power varied within the DOF when tested with Gorilla glass and was not constant as marketed. The highest absorbed power experienced by the glass occurred when the tip of the axicon lens was positioned approximately 7mm from the top surface of the glass. Previous studies on Bessel beam glass cutting have focused on improving the sidewall quality of the cut. However, achieving full separation in a single pass has not been adequately investigated. Current experimental investigation shows that the laser ablated the full depth of the glass at the midsections in a single pass, but was unable to ablate the edges of the glass. A detailed study on the edges of the glass showed that refraction, interfacial spherical aberration and the difference in the speed of light in different mediums prevented the laser from ablating the edges of the glass. A practical approach has been then devised to remove the challenges posed by lack of full depth penetration at the edges and the association fracture pattern. The method ensures that the laser beam is only travelling in the glass throughout the cutting process for the cutting domain of interest. This avoids the difficulties caused by the effects of refraction and the difference in the speed of light in different mediums. Cuts performed with the devised technique had a uniform sidewall profile with minimal defects and full separation at the edges. In summary, this report first investigated the working principles of the Deepcleave module and compared the cutting ability of a shaped Bessel beam to an ordinary Bessel beam. Subsequently the laser parameters were optimized to provide the best sidewall quality for a single pass separation. To achieve this, a practical cutting method was devised to avoid the difficulties associated with the lack of full depth penetration and the associated fracture at the cut edges of the glass.